CURBING STUDENTS’ BULLYING AMONG SECONDARY SCHOOL LEARNERS: THE EFFECTIVENESS OF SCHOOL BULLYING INTERVENTIONS - Joseph Wambua Kioko; Dr Mukirae Njihia, PhD; Sr. Dr. Susan Mutune (PhD) (Galaxy International Interdisciplinary Research Journal, 2024)
The aim of this paper was to examine the effectiveness of bullying interventions in curbing students’ bullying in secondary schools in Machakos County. The study was anchored on social learning theory which expounds on the role played by one’s behavior and how this contributes to bullying among learners. The study used a descriptive survey research design to collect and analyse the primary data. A sample of 333 respondents was selected from a population of 116,053 respondents drawn from 36 schools. A questionnaire and interview guide were used as the key research instruments for the study. The collected data was analysed using both qualitative and quantitative techniques. The findings from the study revealed that students’ bullying among secondary schools in Machakos County was prevalent despite the interventions. It was further revealed that disciplinary interventions such as suspensions and punishments were upheld in most of the schools. Moreover, restorative interventions, anti-bullying programmes, and supportive interventions were found not to be effectively utilized in most of the schools, thus their ineffectiveness in eradicating bullying. The study concluded that bullying among students in secondary schools was prevalent due to ineffectiveness of interventions as they were inadequately implemented. It is therefore recommended that there is need for the school principals and other decision-makers to implement school interventions so as to effectively curb students’ bullying among secondary schools.